Bronchoscopy and central airway disorders : a patient-centered approach - Colt, Henri G.; Murgu, Septimiu; ClinicalKey eBooks (Philadelphia : Elsevier/Saunders, 2012)
Through specifically-designed case scenarios with correlating review questions, this practical respiratory medicine reference leads you through the decision-making process and execution of these sometimes complex procedures, as well as the optimal long-term management of your patients.
Section 1. Practical approach to benign exophytic airway obstruction -- section 2. Practical approach to benign traheal stenosis -- section 3. Practical approach to expiratory central airway collapse -- section 4. Practical approach to mediastinal lymphadenopathy (EBUS and alternatives) -- section 5. Practical approach to malignant central airway obstruction -- section 6. Practical approach to other central airway disease processes -- section 7.
"Expert Consult."
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Bronchoscopy; Bronchi -- Diseases; Bronchi -- Surgery; Respiratory organs -- Obstructions -- Surgery; HEALTH & FITNESS -- Diseases -- Respiratory; MEDICAL -- Pulmonary & Thoracic Medicine; Bronchoscopy -- methods; Bronchial Diseases -- surgery; Airway Obstruction -- surgery; Bronchi -- Diseases; Bronchi -- Surgery; Bronchoscopy; Electronic books